Seasonal changes of photosynthetical parameters as a results of forest gap model - Szalacsi, Árpád; Király, Gergely; Veres, Szilvia (Acta Agraria Debreceniensis, 2015)
Photosynthetic parameters of English oak (Quercus robur L.) as a member of Querco robori-Carpinetum were investigated in two different habitat in terms of gap forest management: in the gap and in the host forest. The artifical opening process of the forest resulted in more light for growing saplings and need for acclimatization. Photosynthesis is one of the most important way for plant life and plant production. In the centre of photosynthetic efficiency the quality and quantity traits of photosynthetic pigments are standing. During our work some photosynthetic parameters of plants (in the gap and in the forest as well) were measured: relative chlorophyll content as SPAD index, chlorophyll a and b content, total chlorophyll content and ratio of chlorophyll a and b. Based on our results no significant differences among our data in early spring. Although, during the summer significant differences occurred between the measured values in the gap and in the forest area. Lower total chlorophyll content was experienced in the gap, than in the forest area due to the lower chlorophyll-b content. Because of the high light intensity higher chla/chlb ratio was measured in the gap. The lower chlorophyll contents of gap habitat may have a part of the acclimatization process of photosynthetic apparatus against high light stress, which can determinate the survival chance of individual.